Quantifying molecular- to cellular-level forces in living cells. (9th September 2021) - Pan, Jason; Kmieciak, Tommy; Liu, Yen-Ting; Wildenradt, Matthew; Chen, Yun-Sheng; Zhao, Yang
Abstract: Mechanical cues have been suggested to play an important role in cell functions and cell fate determination, however, such physical quantities are challenging to directly measure in living cells with single molecule sensitivity and resolution. In this review, we focus on two main technologies that are promising in probing forces at the single molecule level. We review their theoretical fundamentals, recent technical advancements, and future directions, tailored specifically for interrogating mechanosensitive molecules in live cells.